ANALISIS IMPLEMENTASI ALGORITMA A* (A-STAR) PADA GAME RPG (ROLE PLAYING GAME) 3D SEBAGAI DASAR PERGERAKAN NPC (NON-PLAYER CHARACTER) MENDEKATI PLAYER UNTUK MENINGKATKAN REALITAS GAME WORLD - Bonifatius Galih K; Rosa Delima; Samuel Gandang G. (Universitas Kristen Duta Wacana, 2014)
Game is a form of interactivity where player and game world interact to each other. In a game, one of the elements which can be considered necessary to support the course and the reality of the game is how a NPC (Non-Player Character) in the game moves. A* (A-star) is an algorithm which can be used to perform pathfinding. In this case, A* will be used to find a shortest distance between the NPC and the player character. This research was performed to conduct experiments on the implementation of the A* algorithm in the 3D game. The research will be conducted by implementing an A* algorithm to a game, precisely to the enemy characters that exist in the game. Once the implementation was conducted, an experiment will performed using certain cases as a proving ground for the implementation. As a conclusion, from a hundred experiments, A* algorithm always can find the path for enemy to catch player and 73% of them are optimal paths.